Integrating Gender-Sensitive Disaster Risk Management into Community-Driven Development Programs - World Bank (Washington, DC, 2014)
This note on integrating gender-sensitive disaster risk management (DRM) in community-driven development (CDD) Programs is the sixth in a series of guidance notes on gender issues in DRM in the East Asia and the Pacific region. Targeting World Bank staff, clients and development partners, this note gives an overview of the main reasons for incorporating gender-sensitive DRM into CDD programs, identifies the key challenges, and recommends strategies and tools. Poor women and men are more at risk from adverse impacts of natural hazards. Vulnerability to the risks and income shocks resulting from natural disasters is one of the fundamental dimensions of poverty (World Bank, 2009). Many of the communities in which CDD programs are being implemented are disaster-prone and sensitive to the impacts of climate change. Initiatives to strengthen the resilience of poor and vulnerable men and women to natural hazard and climate change impacts can not only contribute to improving their livelihoods and safety but also to protecting the substantial investments being made in poverty reduction, infrastructure and services provision.